Managing collaboration between Traditional and Western health practitioners in mental health care, Limpopo province, South Africa - Nare J. Masola; Mpho Maotoana (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: A significant proportion of South Africa’s black population seeks medical attention from both the traditional and Western health care systems. Traditional health practitioners (THPs) are consulted by many black Africans for the treatment of culturally bounded health problems. However, there is a limited understanding of how to manage the coexistence of traditional and Western health care systems in South Africa, despite government efforts to recognise THPs.